Metode Penyusunan Media Promosi Digital - Hendrik, Dede (LPPM UNIBI, 2024)
The development of information technology is currently felt to be running very fast and has a major influence on all aspects of life, one of the main factors accompanying this development is the internet, which is a large network of interconnections between computers throughout the world through telephone lines, satellites and other telecommunications media. The transmission of information between continents is no longer in a matter of minutes, even at any time someone can access the internet without limits